Implementation of Tazkiyah Al-Nafs Based Islamic Education for Elderly to Achieve Nafs Al-Muthmainnah - Lisning Sri Hapsari; Imas Kania Rahman (Program Studi Pendidikan Agama Islam STAI Auliaurrasyidin Tembilahan, 2022)
One of the stages that every human being will experience is the aging process. In the aging process, the elderly (elderly) is seen as the most important stage. At this stage, every elderly will feel and experience changes and declines that take place naturally, both in terms of physical, psychological, and social changes in dealing with other people. Older people are also often hit by anxiety and worry. They realize that death is getting closer and are increasingly aware of their need for religion, so they are increasingly studying Islam. Islamic education and learning for the elderly require certain learning because the main goal of religious learning for them is to achieve peace and tranquility of mind (nafsmuthmainah) at the Al-Hikmah Islamic boarding school for the elderly, Cibungbulang, Bogor. The purpose of this study was to find out how the implementation of Tazkiyah al-Nafs-based Islamic education for the elderly to achieve Al Muthmainnahnafs which was held at the Al-Hikmah Islamic boarding school in Cibungbulang, Bogor. Implementing a concept of Islamic education for the elderly based on Tazkiyah al-nafs at the Al-Hikmah Cibungbulan Bogor senior boarding school. The method used in this study is qualitative descriptive, namely by describing thought and implementation of Tazkiyah al-Nafs-based Islamic education for the elderly to achieve Al Muthmainnahnafs which is held at the Al-Hikmah Cibungbulang elderly Islamic boarding school. The results of this study are the implementation of Tazkiyah al –Nafs-based Islamic education for the elderly to achieve Al Muthmainnahnafs which is held at the Al-HikmahCibungbulang Bogor elderly boarding school. and weekly and monthly. These activities include praying in congregation 5 times, the habit of fasting sunnah Monday and Thursday, tadarusan after dawn and ashar, and recitations that can support the enthusiasm of the elderly in tazkiyah al-nafs based. As for weekly activities such as fardlukifayah training for the elderly, studying prayers and hadiths, and there are religious lectures and worship coaches, but for monthly activities, it is more about religious tourism to establish friendship and warmth outside of formal education.